A Rational Strategy for Graphene Transfer on Substrates with Rough Features. Issue 12 (25th January 2016) - Hong, Jin‐Yong; Shin, Yong Cheol; Zubair, Ahmad; Mao, Yunwei; Palacios, Tomás; Dresselhaus, Mildred S.; Kim, Sung Hyun; Kong, Jing
Abstract : Graphene grown by chemical vapor deposition is transferred by a very simple, yet effective approach from the growth substrate onto substrates with rough features. This novel and facile method not only results in satisfactory transfer on substrates with terraces or grooves, but also gives rise to a successful result for uneven growth substrates.